INFLUENCE OF PLANT CANOPY AND WEATHER PARAMETERS ON INCIDENCE OF THRIPS (Thrips tabaci Lindemann) IN BT AND NON-BT COTTONS - N. V. V. S. D PRASAD, Y. RAJASEKHAR, P. V. KRISHNAYYA and (The Journal of Research, PJTSAU, 2017)
Studies on influence of plant canopy and weather parameters on the incidence of cotton thrips, Thrips tabaci Lindemann were carried out at Regional Agricultural Research Station, Lam, Guntur during two seasons, kharif 2009-10 and kharif 2010-11. Significantly higher thrips population was recorded at top canopy level followed by middle and bottom irrespective of cotton hybrids/variety. The thrips population was higher during 39th to 41st standard weeks with peak population (no./top 3 leaves/plant) of 7.48, 15.40 and 14.80 in RCH 2 BG II, Mallika BG II and L 604 non-Bt, respectively recorded during 41st std. week. The favourable weather parameters that influenced the buildup of high population of thrips during 39th to 41st std. weeks ranged from 31-35 OC (maximum temperature) and 23-24OC minimum temperatures, morning and evening relative humidities of 77 to 87 and 55 to 74 per cent and the rainfall was 3.00 to 39.00 mm. The population of thrips showed significant positive correlation with maximum and minimum temperatures (r=0.721** and 0.736**), evening relative humidity (r=0.295*) and rainfall (r=0.277*), while a significant and negative association with morning relative humidity (r= -0.605**). The multiple linear regression analysis indicatedthat all the weather variables together contributed to 69.7 per cent variation in thrips population significantly (R2=0.697*). However, minimum temperature and morning relative humidity exerted significant positive and negative influence, respectively on the variation of thrips population independently.